Academic Model of Excellence for Diversification of the Healthcare Workforce...Association of Schools Advancing Health Professions Annual Conference, October 19-21, 2022, The Westin Long Beach, Long Beach, California. - Guglielmo, Mary Jo; McGwire Johnson, Kenya; Bradaric, Brinda; Brasic Royeen, Charlotte (Journal of Allied Health)
Issue: By 2050 in the U.S., non-Hispanic Whites will decrease to 47% and minorities will represent 51% of the population. Racial/ethnic diversity in the healthcare workforce, a type of organizational cultural competence, has been associated with the delivery of quality care to minority populations. Increasing underrepresented groups within the workforce supports the inclusion in and cultural responsiveness of the health professions. Education of a diverse workforce is essential in meeting the healthcare needs of our communities. Method: A baccalaureate health sciences program (BSHS) at academic medical center was designed to provide a bridge to students from community colleges to health studies. Outcomes: Eighty-eight percent of the BSHS undergraduates (a majority who identified as underrepresented minorities in healthcare) are pursuing or have completed graduate education or additional studies in healthcare fields. Conclusion: The structure, interventions and culture of the health sciences program resulted in successful promotion of diversification to the healthcare workforce.